2007
DOI: 10.1667/rr0829.1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Integrins and PI3K/Akt-Mediated Signal Transduction Pathways Enhances Radiation-Induced Anti-angiogenesis

Abstract: The integrins and PI3K/Akt are important mediators of the signal transduction pathways involved in tumor angiogenesis and cell survival after exposure to ionizing radiation. Selective targeting of either integrins or PI3K/Akt can radiosensitize tumors. In this study, we tested the hypothesis that the combined inhibition of integrin alphanubeta3 by cRGD and PI3K/Akt by LY294002 would significantly enhance radiation-induced inhibition of angiogenesis by vascular endothelial cells. Treatment with cRGD inhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…PI3K/Akt signaling is well characterized with respect to promoting cell survival and suppressing apoptosis. There is evidence that PI3K pathway inhibition enhances radiation-induced antiangiogenesis and increases tumor radiosensitivity by normalizing the tumor vasculature (38,39). Our data showed that radiation activated FAK-PI3K/Akt signaling.…”
Section: Discussionsupporting
confidence: 51%
“…PI3K/Akt signaling is well characterized with respect to promoting cell survival and suppressing apoptosis. There is evidence that PI3K pathway inhibition enhances radiation-induced antiangiogenesis and increases tumor radiosensitivity by normalizing the tumor vasculature (38,39). Our data showed that radiation activated FAK-PI3K/Akt signaling.…”
Section: Discussionsupporting
confidence: 51%
“…21 Integrins are key regulators of angiogenesis by controlling signal transduction. 22 In conjunction with other pro-angiogenic factors, they are key to migration, adhesion, proliferation and differentiation of EC. Tumour research has identified two integrins important in tumour angiogenesis, amb3 and amb5, that are highly expressed not only on some tumour cells, but also on neurovascular EC.…”
Section: Angiogenesismentioning
confidence: 99%
“…The amb3 signalling that occurs after irradiation can be interrupted by coadministration of the integrin binding cyclic Arg-Gly-Asp (cRGD) peptide; 25 blocking the interaction between amb3 and its natural ligands results in adhesion disruption, detachment of EC from the matrix and increased levels of apoptosis. 22 …”
Section: Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…To fully assess the effects of intetumumab on radiation response of tumors and interaction of tumor cells and their microenvironments, we next studied the combined use of intetumumab and fractionated local tumor radiation therapy in nude rats with human cancer xenograft. Based on our previous studies (5,8,9), we hypothesized that intetumumab would potentiate the efficacy of fractionated radiation therapy and inhibit tumor metastasis by blocking the function of adhesion molecules in the microenvironment of potential metastatic sites.…”
Section: Introductionmentioning
confidence: 99%